Benefit of a pharmacist-led intervention for medication management of renal transplant patients: a controlled before-and-after study - Chambord, Jeremy; Couzi, Lionel; Merville, Pierre; Moreau, Karine; Xuereb, Fabien; Djabarouti, Sarah (Therapeutic advances in chronic disease, 2021)
Aims: To assess the effect of a pharmacist-led intervention, using Barrows cards method, during the first year after renal transplantation, on patient knowledge about their treatment, medication adherence and exposure to treatment in a French cohort. Methods: We conducted a before-and-after comparative study between two groups of patients: those who benefited from a complementary pharmacist-led intervention [intervention group (IG), n = 44] versus those who did not [control group (CG), n = 48]. The pharmacist-led intervention consisted of a behavioral and educational interview at the first visit (visit 1). The intervention was assessed 4 months later at the second visit (visit 2), using the following endpoints: treatment knowledge, medication adherence [proportion of days covered (PDC) by immunosuppressive therapy] and tacrolimus exposure. Results: At visit 2, IG patients achieved a significantly higher knowledge score than CG patients (83.3% versus 72.2%, p = 0.001). We did not find any differences in treatment exposure or medication adherence; however, the intervention tended to reduce the proportion of non-adherent patients with low knowledge scores. Using the PDC by immunosuppressive therapy, we identified 10 non-adherent patients (10.9%) at visit 1 and six at visit 2. Conclusions: Our intervention showed a positive effect on patient knowledge about their treatment. However, our results did not show any improvement in overall medication adherence, which was likely to be because of the initially high level of adherence in our study population. Nevertheless, the intervention appears to have improved adherence in non-adherent patients with low knowledge scores.